Newsletter As A Promotion Media Of Japan Indonesia Network - Haulia Siti Nurfadilah; Ningrum Tresnasari (Universitas WIdyatama, 2020)
Newsletters are the latest media publications that contain important product information and are starting to be used as an appropriate marketing strategy in business. One company that uses newsletters as a promotional media is JIN (Japan Indonesia Network). This study aims to determine the types of newsletters used by JIN as promotional media and also to explain the advantages and disadvantages of the newsletters used by JIN as a promotional media. The research data used in this research are newsletters that have been published by JIN periodically. The research method used is descriptive qualitative. The type of newsletter that JIN uses as a promotional media is the customers newsletter. In addition, the advantage of using newsletters as a promotional media is that it is practical in informing a product to customers, while the disadvantage is that the newsletter display used by JIN is still considered less attractive by customers.